Louis Braille, the boy who invented books for the blind - Davidson, Margaret, 1936-; Compere, Janet (New York : Scholastic, 1971)
The life of the 19th-century Frenchman who invented an alphabet enabling the blind to read.
Includes braille alphabet on back cover.
510
510
Accelerated Reader AR
Keywords: Braille, Louis, -- 1809-1852 -- Juvenile literature; Braille, Louis, -- 1809-1852.; Blind; People with disabilities; Blind -- Printing and writing systems